Influence of Dimethyl Sulfoxide Solutions and Incubation Temperature on Functional Activity of Individual Adrenal Cell Populations of Rats - Dudetskaya, Galyna; Bondarenko, Tatyana (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 287